The place is in Fadwa Toukan’s poetry - سلمان القضاه محمود فليح; طه الحراحشه منتهى (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
Place is one of the most important topics for the study of literary works. It is also the essence and basis of the creative process. Thus, the aim of this study is to study place and explain its importance and manifestations in the poetry of FadwaTouqan- one of the most prominent Palestinian poets who demonstrated place in their poems with the same space and identity of their own. As place is strongly present in the poetry of FadwaTouqan, it is necessary to study her poetic works and link it to the references of the place and its connotations and the dimensions it carries. Place in FadwaTouqan’s poetry is not a mere geographical dimension but also a representative for a group of psychological signals and intellectual and esthetic visions. The poet, via these signals and visions, expresses her human, political, and social reality by a set of dimensions that are represented in a group of prominent dualities. The first duality is about place, love and hope. The second one is about place, sadness, and alienation. Finally, there is place and national concern.